Effect of Stocking Density on Water Quality, Harmful Nitrogen Control, and Production Performance of Penaeus vannamei in Biofloc-Based Systems with Limited Water Exchange - Wujie Xu; Bin Zhang; Yongzhen Zhao; Yucheng Cao (Fishes)
Biofloc technology (BFT) represents a promising approach among sustainable options for the sustainable intensification of shrimp aquaculture, helping to mitigate environmental impacts while maintaining production yields. This study evaluated the effects of stocking density (200, 400, 600, and 800 ind/m3) on the water quality, nitrogen dynamics, and production performance of Penaeus vannamei in BFT systems with limited water exchange (<10%). During an eight-week production-scale trial, water quality exhibited density-dependent deterioration, with TAN and NO2−-N peaks increasing from 0.4 to 2.3 mg/L and 1.0 to 4.2 mg/L, respectively, as density rose from 200 to 800 ind/m3. Concurrently, DO and pH declined significantly from 6.7 to 5.1 mg/L and 7.6 to 7.3, respectively. Production performance revealed critical trade-offs: while yield rose from 3.62 to 9.09 kg/m3, individual growth metrics declined, including harvest body weight (19.14 to 14.12 g), size variation (14.03% to 23.90%), and survival rate (94.6% to 79.8%). Quadratic regression analysis and response surface analysis identified 400~600 ind/m3 as the optimal density range, achieving balanced outcomes: yield (6.74~8.43 kg/m3), harvest body weight (16.72~18.03 g), survival rate (84.0%~93.5%), and feed conversion ratio (1.14~1.22). These findings provide actionable guidelines for optimizing stocking density in commercial BFT systems, highlighting the importance of balancing productivity with environmental sustainability under limited water exchange.